2016
DOI: 10.1111/jocn.13135
|View full text |Cite
|
Sign up to set email alerts
|

Refusal to participate in heart failure studies: do age and gender matter?

Abstract: Aims and objectives The objective of this retrospective study was to evaluate reasons heart failure patients decline study participation, to inform interventions to improve enrollment. Background Failure to enrol older heart failure patients (age > 65) and women in studies may lead to sampling bias, threatening study validity. Design This study was a retrospective analysis of refusal data from four heart failure studies that enrolled 788 patients in four states. Methods Chi-Square and a pooled t-test wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
3
12
2
Order By: Relevance
“…This discomfort with randomization has been confirmed in previous surgical intervention studies [11]. Consistent with other work [1, 12], our analysis found that disinterest was a common reason for participation refusal, particularly in the device study. Previous work investigating home health monitoring devices suggests that patients often have no interest in using a device or they perceive it as unnecessary [13].…”
Section: Discussionsupporting
confidence: 91%
“…This discomfort with randomization has been confirmed in previous surgical intervention studies [11]. Consistent with other work [1, 12], our analysis found that disinterest was a common reason for participation refusal, particularly in the device study. Previous work investigating home health monitoring devices suggests that patients often have no interest in using a device or they perceive it as unnecessary [13].…”
Section: Discussionsupporting
confidence: 91%
“…Although according to the CDC, 45 there is a minimal difference in diabetes rates among men (6.6%) and women (5.9%), studies show that reasons for refusing to participate in studies is the same among men and women. [46][47][48] Participants of this study were recruited, engaged and retained; there was an 84.4% retention rate for the entire 12 months of the study, with only 15.6% lost to follow-up. Retention rates were similar in the IG and CG groups (90% and 88%, respectively) and slightly lower in the ACG group (75%; Table 2).…”
Section: Demographicsmentioning
confidence: 99%
“…Research participants are likely to be younger than those who decline to participate [6, 26, 37–41]. Decliners have also been found to have lower levels of education [7, 41, 42] and lower QOL [42], worse health [37, 38, 41, 4345], more cognitive impairment [45] and higher levels of perceived social support [41] compared to participants. The role of gender is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…The role of gender is less clear. Some studies show that men are more likely than women to participate in health-related research [7, 26, 39, 40], while others demonstrate the opposite [46] or no [38] effect. Lack of time and competing tasks have been described as further reasons for declining participation in health-related research [33, 38, 4749], and in some cases the lack of time was due to care-related activities [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation